Macroeconomic Policy Lessons for Greece from the Debt Crisis - George Economides; Dimitris Papageorgiou; Apostolis Philippopoulos (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper first searches for the drivers of the Greek depression in the aftermath of the 2007-8 global crisis and in turn looks for engines of sustained growth. We use a micro-founded macroeconomic model calibrated to Greece. Our simulations show that the adopted adjustment program (namely, the fiscal austerity mix combined with the fiscal and monetary bailouts by the EU, ECB and IMF), jointly with the observed deterioration in institutional quality (specifically, in the degree of protection of property rights) can explain most (around 22% of GDP) of the cumulative loss in GDP in the data (around 24% of GDP) between 2009 and 2016. In particular, the adjustment program can explain a fall of around 12%, while the deterioration in property rights accounts for another 10%. Counterfactual simulations, on the other hand, show that the cumulative output loss could have been around 9% only, if the country had followed a different fiscal policy mix; if the degree of product marker liberalization was closer to that in the core euro zone countries; and, above all, if institutional quality in Greece had simply remained at its pre-crisis level. On the other hand, we show that, in the absence of the official fiscal bailouts, the depression would be much deeper, while the accommodative role played by the quantitative policies of the ECB has been vital to the Greek economy.
Keywords: O40; H60; E02; 330; growth; macroeconomic policy; institutions